PENGARUH GAYA KEPEMIMPINAN TERHADAP KINERJA KARYAWAN PT PERTAMINA (PERSERO) UP II SUNGAI PAKNING - Silva Ardelia; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Style of leadership is the ability to direct, influence, encourage and control others orsubordinates to be able to do something on his consciousness and voluntary work inachieving a certain goal. A leader in the company's leadership is very important because aperson's leadership the company leaders will affect the overall performance of employees inevery aspect, in which the employee's performance will have an impact in achievingcorporate goals. Looking at the times of rapid change, the most effective style is situationalleadership style where the leader must be able to adapt his style according to the situationand conditions.Performance is the result of work that can be accomplished by a person or group ofpeople in an organization, in accordance with the authority and responsibilities of each, inorder to achieve the goals of the organization in question legally, do not violate the law andin accordance with moral and ethical and evaluated by a particular person.This research was conducted at PT Pertamina (Persero) UP II Sungai Pakninglocated in Jalan Cendana, Pertamina complex, Sungai Pakning. The purpose of this researchwas conducted to determine the effect of leadership style on the performance of employees ofPT Pertamina (Persero) UP II Sungai Pakning.In this research methodology used is descriptive and quantitative with SPSS, wherethe samples used were employees of PT Pertamina (Persero) UP II Sungai Pakning and as asource of information is the HRD and Manager. To determine the sample using Slovinformula, method of stratified proportional sampling. Data collection through interviews,observation and questionnaires.From the analysis of data that includes the test of validity, reliability, and simplelinear regression, situational leadership style in this study includes four components of boththe telling, selling, partivipating, and delegating. Each has indicators that are interrelatedand positive influence on the performance of employees of PT Pertamina (Persero) UP IISungai Pakning .Keywords: leadership style, performance